Allergen immunotherapy in polysensitized patients - Kowal, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
Allergen immunotherapy (AIT) is effective in treatment of allergic diseases including allergic rhinoconjunctivitis and allergic asthma. The majority of allergic patients are sensitized to at least two non-related allergens. Only a few controlled clinical studies report results concerning efficacy of AIT in polysensitized patients. Allergen immunotherapy with a single allergen in polysensitized patients is effective during AIT. In patients sensitized to two non-related allergens AIT with two non-related allergens seems to be more effective than AIT with any allergen alone. Before starting AIT it is very important to establish to which allergens sensitization is clinically important. Making a decision about AIT with two or more allergens one should keep in mind that efficacy of AIT depends on achieving an appropriate dose of major allergens. Further controlled studies are necessary to address the efficacy and safety of AIT in polysensitized patients.